ANALYSIS OF FRAUD DIAMOND DIMENSION IN DETECTING FINANCIAL STATEMENT FRAUD - Nia Susnita Sari; Arifin Sofyan; Nada Fastaqlaili (Jurnal Akuntansi Trisakti, 2018)
This research aims to examine and prove the effectiveness of the fraud diamond in detecting financial statement fraud. The element of the fraud diamond that is used as independent variables is a pressure with proxy financial stability and external pressure, opportunity with proxy ineffective monitoring and nature of the industry, rationalization with proxy auditor change and capability with proxy positioning. In this research uses the F-Score model to measure financial statement fraud as the dependent variable. The population of this research is the manufacturing companies from sub-sector consumer goods listed in Indonesia Stock Exchange in 2015-2017. Sampling from this study uses purposive sampling method and obtained 97 samples with hypothesis testing using multiple linear regression. The results indicate that the external pressure and nature of the industry has a significant positive effect on financial statement fraud. Meanwhile, financial stability, ineffective monitoring, rationalization, and positioning does not affect financial statement fraud.